JAG consensus statements for training and certification in colonoscopy. Issue 3 (27th January 2023) - Siau, Keith; Pelitari, Stavroula; Green, Susi; McKaig, Brian; Rajendran, Arun; Feeney, Mark; Thoufeeq, Mo; Anderson, John; Ravindran, Vathsan; Hagan, Paul; Cripps, Neil; Beales, Ian L P; et al.
Abstract : Introduction: In the UK, endoscopy certification is awarded when trainees attain minimum competency standards for independent practice. A national evidence-based review was undertaken to update and develop standards and recommendations for colonoscopy training and certification. Methods: Under the oversight of the Joint Advisory Group (JAG), a modified Delphi process was conducted between 2019 and 2020 with multisociety expert representation. Following literature review and Grading of Recommendations, Assessment, Development and Evaluations appraisal, recommendation statements on colonoscopy training and certification were formulated and subjected to anonymous voting to obtain consensus. Accepted statements were peer reviewed by JAG and relevant stakeholders for incorporation into the updated colonoscopy certification pathway. Results: In total, 45 recommendation statements were generated under the domains of: definition of competence (13), acquisition of competence (20), assessment of competence (8) and postcertification support (4). The consensus process led to revised criteria for colonoscopy certification, comprising: (1) achieving key performance indicators defined within British Society of Gastroenterology standards (ie, unassisted caecal intubation rate >90%, rectal retroversion >90%, polyp detection rate >15%+, polyp retrieval rate >90%, patient comfort <10% with moderate–severe discomfort); (2) minimum procedure count 280+; (3) performing 15+ procedures over the preceding 3 months; (4) attendance of the JAG Basic Skills in Colonoscopy course; (5) terminal ileal intubation rates of 60%+ in inflammatory bowel disease; (6) satisfying requirements for formative direct observation of procedure skills (DOPS) and direct observation of polypectomy skills (Size, Morphology, Site, Access (SMSA) level 2); (7) evidence of reflective practice as documented on the JAG Endoscopy Training System reflection tool; (8) successful performance in summative DOPS. Conclusion: The UK standards for training and certification in colonoscopy have been updated, culminating in a single-stage certification process with emphasis on polypectomy competency (SMSA Level 2+). These standards are intended to support training, improve standards of colonoscopy and polypectomy, and provide support to the newly independent practitioner.